2014
DOI: 10.1155/2014/540292
|View full text |Cite
|
Sign up to set email alerts
|

Fungi Treated with Small Chemicals Exhibit Increased Antimicrobial Activity against Facultative Bacterial and Yeast Pathogens

Abstract: For decades, fungi have been the main source for the discovery of novel antimicrobial drugs. Recent sequencing efforts revealed a still high number of so far unknown “cryptic” secondary metabolites. The production of these metabolites is presumably epigenetically silenced under standard laboratory conditions. In this study, we investigated the effect of six small mass chemicals, of which some are known to act as epigenetic modulators, on the production of antimicrobial compounds in 54 spore forming fungi. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…DMSO is a polar solvent that has the ability to dissolve a wide range of compounds and is miscible with most solvents [45]. Zutz et al [46] found that DMSO up to a concentration of 2.5% did not alter the growth of C. albicans. In this study, DMSO was used at a final concentration of 3% and it was noted it had a growth stimulatory effect at all tested concentrations on C. krusei only.…”
Section: Discussionmentioning
confidence: 99%
“…DMSO is a polar solvent that has the ability to dissolve a wide range of compounds and is miscible with most solvents [45]. Zutz et al [46] found that DMSO up to a concentration of 2.5% did not alter the growth of C. albicans. In this study, DMSO was used at a final concentration of 3% and it was noted it had a growth stimulatory effect at all tested concentrations on C. krusei only.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial activity testing was performed as previously described ( Zutz et al, 2014 ). Additionally to the indicator organisms S. aureus, Candida ( C. ) albicans and Pseudomonas ( P. ) aeruginosa we used also Klebsiella ( K. ) pneumoniae, Staphylococcus ( S .)…”
Section: Methodsmentioning
confidence: 99%
“…In a previous work we have established a screening system based on the use of such low molecular weight molecules, like VPA, to induce the production of “cryptic” antimicrobial compounds in fungi ( Zutz et al, 2014 ). In this work we focused on one hit candidate, the fungus D .…”
Section: Introductionmentioning
confidence: 99%
“…activation of epigenetic factors) [35,36]. Whereas the former require a priori knowledge of a specific BGC [37][38][39], the latter are less-specific and modify global gene expression with direct and indirect consequences on the expression of multiple BGCs [40][41][42][43][44][45][46][47]. Further pleiotropic approaches rely on variations of the growth media (e.g.…”
Section: A Shot In the Dark: Approaches To Activate The Silent Microbmentioning
confidence: 99%
“…Further general approaches for "genome mining" rely on epigenetic factors involved in chromatin remodeling or global gene expression, either by using mutants or by adding exogenously chemical elicitors like valproic acid, 5-azacytidine or suberoylanilide hydroxamic acid [41][42][43][45][46][47]145,146]; on the exogenous addition of chemicals like GlcNAc, cAMP, FA synthesis inhibitors, antibiotics or quorum sensing molecules [29,81,139,140,147,148], rare earth elements like scandium [149];…”
Section: Box 2 On the Ways To Activate The Microbial Secondary Metabmentioning
confidence: 99%